The dynamics and transmission of antibiotic resistance associated with plant microbiomes - Chen, Ping; Yu, Kaifeng; He, Yiliang (Environment international, 2023)
[Display omitted] •ARGs in plant microbiomes are affected by rhizosphere microbiomes and root exudates.•The specific intrinsic genes of plants may determine the types of root exudates.•The intrinsic genes of plants may have the potential to encode antibiotic resistance.•Phyllosphere microorganisms and endophytes affect ARGs in plant microbiomes.•ARGs in plant microbiomes come from a wide range of sources. Antibiotic resistance genes (ARGs) have been widely found and studied in soil and water environments. However, the propagation of ARGs in plant microbiomes has attracted insufficient attention. Plant microbiomes, especially the rhizosphere microorganisms, are closely connected with water, soil, and air, which allows ARGs to spread widely in ecosystems and pose a threat to human health after entering the human body with bacteria. Therefore, it is necessary to deeply understand and explore the dynamics and the transmission of ARGs in rhizosphere microorganisms and endophytes of plants. In this review, the transmission and influencing factors of ARGs in the microorganisms associated with plants, especially the influence of root exudates on plant microbiomes, are analyzed. Notably, the role of intrinsic genes of plants in determining root exudates and their potential effects on ARGs are proposed and analyzed. The important role of phyllosphere microorganisms and endophytes in the transmission of ARGs and co-resistance of antibiotics and other substances are also emphasized. The proliferation and transmission of ARGs associated with plant microbiomes addressed in this review is conducive to revealing the fate of ARGs in plant microorganisms and alleviating ARG pollution.